1993
DOI: 10.1111/j.1432-1033.1993.tb18366.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant coho salmon insulin‐like growth factor I

Abstract: Recombinant coho salmon insulin-like growth factor I (rsIGF-I) was produced in Escherichia coli, purified and characterized. The rsIGF-I expression vector was constructed by polymerase chain reaction and cloning into a plasmid containing a phage T7 RNA polymerase promoter. The rsIGF-I was recovered from bacterial inclusion bodies, solubilized under reducing conditions, immediately refolded, then fractionated by a two-step ion-exchange chromatography on DEAE-52 and Mono-S columns. It was further purified by HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 33 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…This might be due to the fact that we used rhIGFs, which are 80% homologous to teleost IGFs [9]. In a study carried out on coho salmon, Moriyama et al [10] found that the IGF-I plasma levels vary between 45.2 Ϯ 5.4 and 117.4 Ϯ 19.1 ng/ml, placing our effective concentrations within the range found in the plasma of another teleost species and confirming that the positive effects of IGFs observed in our experiment are not pharmacological.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This might be due to the fact that we used rhIGFs, which are 80% homologous to teleost IGFs [9]. In a study carried out on coho salmon, Moriyama et al [10] found that the IGF-I plasma levels vary between 45.2 Ϯ 5.4 and 117.4 Ϯ 19.1 ng/ml, placing our effective concentrations within the range found in the plasma of another teleost species and confirming that the positive effects of IGFs observed in our experiment are not pharmacological.…”
Section: Discussionmentioning
confidence: 96%
“…Both IGF-I and -II are mitogenic peptide hormones that play an important role in the regulation of growth, differentiation, regeneration, and metabolism [7]. IGF-I is mainly produced in the liver [8][9][10] and has been known for some time to mediate most of the growth-promoting actions of growth hormone (GH) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of IGFs in these species has not been extensively characterised and it remains to be determined if IGFs have been functionally as well as structurally conserved throughout vertebrate evolution. While in vitro characterisation of salmon (Moriyama et al 1993), trout (Moriyama et al 1995) and chicken (Dawe et al 1988, Armstrong et al 1990, Kallincos et al 1990, Upton et al 1992) IGF-I has been described, very few in vivo studies using homologous proteins have been performed. Marsupials (metatherians) diverged most recently from placental mammals (eutherians) and are thought to have potential as developmental models (Tyndale-Biscoe & Janssens 1988).…”
Section: Introductionmentioning
confidence: 99%
“…But the impact of molecular genetics on fisheries will not stop there. Our ability to examine and manipulate molecules has increased phenomenally -if we choose, we can even make transgenic fish (Devlin, 1993), or express recombinant fish proteins (Moriyama et aL, 1993). Research using these techniques can help elucidate the roles of various genes in reproduction, growth, etc.…”
Section: The Future Of Molecular Genetics In Fisheriesmentioning
confidence: 99%